ISLAMIC WORLDVIEW ANTARA WACANA DAN PROBLEMATIKA DALAM KONSTRUKSI PSIKOLOGI ISLAM - Syahri Ramadhan; Nelia Guswanti (Jurnal Al-Karim : Jurnal Pendidikan, Psikologi dan Studi Islam, 2024)
Despite of receiving appreciation, the development of Islamic Psychology, especially in Indonesia, has also gained various criticisms from various psychology practitioners and academics. Among the topics that became discourses was Islamic Worldview in Islamic Psychology. This article seeks to answer the problems surrounding the discourse and problems of Islamic Worldview discourse in the construction of Islamic Psychology. The research method used is a qualitative descriptive method with the type of field research. The research informants were determined by purposive sampling with the criteria of scientists and practitioners of Islamic Psychology, academics and psychology students totaling four people. Data were collected by interview, observation and documentation methods. The data was analyzed using the Miles and Hubberman qualitative data analysis model, namely data reduction, data display, and data verification. The results of the study show that the discourse on the construction of Islamic Psychology is very enthusiastically welcomed by psychological scientists. The content of the discourse is to build Psychology with a new perspective that is different from Western Psychology, by making the Qur'an and hadith the main source of Islamic Psychology. However, the problem is that 1) Western Psychology has dominated and has an established scientific construction, while Islamic Psychology is just trying to formulate, 2) Not all, even most Muslim Psychology scientists do not master Arabic which incidentally is the language of the Qur'an and hadith, 3) There is still a low understanding of Muslim students who study Psychology in universities about Islamic teachings, 4) The recognition of the existence of Islamic Psychology as one of the disciplines is still questionable and does not have strong legality in the laws and regulations regarding higher education. With this research, it is hoped that it will be able to spark further discussions about the existence of Islamic Psychology as part of the psychology discipline that has the right to legal legality in universities and motivate Muslim psychology scientists to be committed and consistent in studying Islamic Psychology in terms of kaffah (totality).